Vertebral artery hypoplasia does not influence lesion size and clinical severity in acute ischemic stroke - Sauer, Tamara; Wolf, Marc; Ebert, Anne; Szabo, Kristina; Chatzikonstantinou, Anastasios (Journal of stroke and cerebrovascular diseases, 2016)
Background - Vertebral artery hypoplasia (VAH) is common, but its role in acute ischemic stroke (AIS) is uncertain. We aimed to evaluate the frequency, characteristics, and role of VAH in a large typical cohort of patients with AIS. - Methods - Up to 815 AIS patients (52.8% men, mean age 70 ± 14 years) were included in the study. All patients received a stroke work-up including brain imaging and duplex ultrasound. VAH was defined by a vessel diameter of less than or equal to 2.5 mm or a difference to the contralateral side of greater than 1:1.7. Vascular risk factors and stroke features were recorded. The subgroup of patients with posterior circulation AIS and magnetic resonance imaging was analyzed additionally, including the parameter of stroke extent. - Results - Up to 111 patients (13.6%) had VAH, with a mean diameter of 2.4 ± .4 mm. Patients with VAH were significantly younger (P = .037) and more often male (P = .033). There was no difference considering the National Institutes of Health Stroke Scale and modified Rankin Scale scores on admission or history of stroke. The distribution of patients without VAH was significantly different among the groups with anterior, posterior, and both circulations ischemia (P = .009). In the group with posterior circulation stroke, 36 patients (20.9%) had VAH. There were no differences in age, sex, history of stroke, risk factors, vascular territory, stroke size, or etiology. VAH patients had less often embolic stroke patterns (P = .009). - Conclusions - VAH is more common in patients with posterior circulation stroke and in younger patients. Apart from that, we found no clear evidence that VAH would be a predisposing factor for stroke or that it increased the risk for larger ischemic lesions in the posterior circulation.